THE EFFECTIVENESS OF ENGLISH TEACHING MATERIALS USING TECHNOLOGY TO ENHANCE HIGHER ORDER THINKING SKILLS (HOTS) - Rona Rossa; Winda Noprina; Rahmia Tulljanah (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Higher order thinking skills should be included into all aspects of teaching and learning, particularly at the university level in facing digital society 5.0. Teachers must be able to incorporate such abilities into their courses, including their curriculum, syllabus, lesson plan, teaching approach, and teaching materials, as well as their English classes, based on this issue. English teaching materials by using technology is one of innovative way to facing the need of digital society 5.0. This study investigates the effectiveness of English teaching materials by using technology for university students. This research is experimental research in the form of pre-test and post-test control group design. This research was conducted on the first-year students of Adzkia University in the year 2021/2022. The instrument used in this study is the test. It is used to assess students' higher order thinking skills. SPSS was used to analyze the test data quantitatively. From results of the study, it is found that students who are taught by English teaching materials using technology have better higher order thinking skills than the students who are taught by using conventional English teaching materials. It can be concluded that English teaching materials is effective media to enhance higher order thinking skills (HOTS).